Pengaruh Online Shop Dan Harga Terhadap Minat Beli Barang Secara Online Pada Karyawan Toko Sinar Welisa Jaya Di Citraland Surabaya - Dani Feki Kris Koro; Achmad Daengs GS; Sugiharto Sugiharto; Rina Dewi; Harsono Teguh Santoso (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of online shop and price on the intention to buy online among Toko Sinar Welisa Jaya employees. The research method used is a quantitative method. The processed data is the result of a questionnaire with a population of 364 and a sample of 78 respondents. The data analysis technique used is the classical assumption test which consists of a normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis, as well as hypothesis testing, namely the coefficient of determination, f test, t test. The results of the research based on the tests produced show that online shops and prices have a significant influence on online buying interest among employees at the Sinar Welisa Jaya in Citraland Surabaya store, one of which is evidenced by the results of the determination coefficient that the correlation between employee buying interest and all independent variables (online shop and price) R-Square of 0.773 means that 77.30% variation or change in employee buying interest is jointly influenced by online shop and price while the remaining 22.70% variation or change in employee buying interest is caused by other variables that are not included in this study.